ANALISIS SIKAP SOSIAL DAN PERMASALAHAN DALAM PEMBELAJARAN MENULIS TEKS EDITORIAL PADA SISWA KELAS XII SMAN 1 SUKAGUMIWANG TAHUN AJARAN 2024/2025 - Nova Yuliana; Irfan Efendi; Ahmad Maskur Subaweh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education is something that can support the quality of a nation, with education it can produce the nation's next generation who are qualified and have good knowledge and abilities. Apart from mastering knowledge, social and moral education is also important for students to obtain. The aim of this research is to analyze social attitudes and find out the problems that occur in learning to write editorial texts among class XII students at SMAN 1 Sukagumiwang for the 2024/2025 academic year. The method used in this research is focused interviews using a qualitative approach. The instruments used were observation sheets carried out by teachers on students, and interviews conducted by researchers with Indonesian Language Teachers at SMAN 1 Sukagumiwang. The research results revealed that there were several stages of assessment carried out by teachers, namely planning, implementing and reporting assessments of students' social attitudes. This research also has problems in editorial text learning activities, namely the lack of students' ability to write editorial texts which is influenced by students' social attitudes.